Hutan Lestari, Masyarakat Sejahtera: Best Practice dari Desa Burno Kabupaten Lumajang - Nisak, Fitrotun; Jannah, Raudlatul (International Conference on Multidisciplinary Issues (INCOMI), 2024)
Implementation of social forestry policies has different impacts in each region. This research wants to answer 1) how social forestry is managed in Burno Village?; 2) what challenges are faced in the sustainability of social forestry practices in Burno Village? and 3) What social values are practiced by local communities to preserve forests? James S. Coleman’s social capital theory is used in this study. The method used is a qualitative method with a phenomenological approach. Data collection techniques were done through observation, in-depth interviews, and documentation. The results of this research show that the forest land management strategy by the Burno Village pesanggem is carried out with a management concept that benefits farmers, builds strong institutions, and keeps forests sustainable. There are local community values and strong social capital in the community, so management can run well.